WAWASAN DAN PERSEPSI GURU BAHASA INDONESIA TERHADAP PROGRAM PENGINTEGRASIAN MATERI ANTI-KKN DALAM PEMBELAJARAN BAHASA INDONESIA - Sumadi Sumadi (Fakultas Sastra Universitas Negeri Malang, 2012)
Teachers have very strategic role in abolishing corruption, collusion and nepotism in Indonesia which has been a level of apprehensive. It can be done because through education, teachers can internalize the values of anti corruption, collusion and nepotism to the next generation of the nation naturally, programming and systematically. This research aims to reveal the teachers’ vision and perceptiontoward the program of integrating anti corruption, collusion and nepotism material in the teaching-learning process of Indonesian language. The result of this research can be used as a starting point in integrating the material of anti corruption, collusion and nepotism in Indonesian teaching-learning process.